A systematization model for quantitative game analysis - Winter, C.; Pfeiffer, M. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
From the perspectives of training and exercise science and performance analysis on sports games, it is particularly important to analyze the competition. As a result of technological progress, a broad spectrum of different approaches to game analysis has developed in this field in recent years. A systematization model of quantitative match analysis is presented, which facilitates orientation and enables the comparison of studies on different levels. For this purpose, the decisions required for the various steps of the analysis are subdivided into data collection, registration of basic elements of tactical behaviour and aggregation. The model can be used to categorize published studies as well as to plan future game analyses for performance analysis.